Sustainability Reporting and Earnings Management Engagement from An Emerging Economy Perspective - Elena Turuianu (Nechita) (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Question- To what extent does the disclosure of non-financial information by companies listed on BSE after the adoption of the EU directive lead to a decrease in the use of earnings manipulation techniques? Motivation- In line with the Sustainable Development Goals (SDGs) developed by the United Nations (UN) in 2015, as well as the worldwide spreading requirements related to the disclosure of non-financial information, the influence of sustainability and non-financial reporting on firms' engagement in earnings management practices is investigated through a pre-post adoption of European Directive 2014/95/EU comparative analysis for firms listed on the Bucharest Stock Exchange (BSE) in the period 2015-2019. Idea- The study aims to analyse the influence of sustainability and non-financial reporting on companies' engagement in earnings management practices. Data and tools- To conduct the investigation, the research involves the assessment and analysis of three earnings management metrics resulted by running multiple linear regression models on a sample of 31 companies listed on BSE. Findings- Research findings emphasise a decrease in the use of income smoothing practices by sampled companies in the post-adoption period 2017-2019, compared to the period preceding the implementation of the EU directive related to mandatory disclosure of non-financial information, 2015-2016. Thus, firms characterised by a higher transparency in terms of sustainability reporting are less inclined to engage in earnings management practices. Contribution- This research complements the literature in the field of sustainability reporting and earnings management, providing empirical evidence on the significance and impact of publishing non-financial information, the results being noteworthy for both investors and standard setters.
Keywords: M40; M41; Q56; 650; sustainability reporting; earnings management; European Directive 2014/95/EU; non-financial re-porting; sustainable development goals (SDGs); empirical research